Patient and Provider Experience With Cystic Fibrosis Telemedicine Clinic - Hendra, Kalen; Neemuchwala, Fatima; Chan, Marilynn; Ly, Ngoc P.; Gibb, Elizabeth R. (Frontiers in Pediatrics, 2021)
In response to the novel coronavirus (COVID-19) pandemic, all in-person cystic fibrosis (CF) appointments were converted to telemedicine visits at UCSF Benioff Children’s Hospital. The purpose of our study was to learn about the experiences that patients, families, and providers had with telemedicine visits and to assess their interest in using telemedicine in the future. Our hypothesis was that most patients, families, and providers want to continue telemedicine visits in the future. An anonymous 11-question survey was distributed to patients, families, and providers in November and December 2020. The survey was completed by 46 of 72 families (64% response rate) and 24 of 25 providers (96% response rate). Thirty-seven families (80%) and 21 providers (88%) were satisfied with their telemedicine experience. Thirty-three families (72%) want to have telemedicine visits in the future. Thirty-five families (76%) and 22 providers (92%) were satisfied with their experience using Zoom. Forty families (87%) and 19 providers (90%) want 2 or more visits each year to be via telemedicine. Our study showed that most families and providers were satisfied with telemedicine, would like to continue using telemedicine, and prefer to have at least 2 of the 4 recommended annual CF visits via telemedicine. Our survey identified the following benefits to telemedicine: decreased travel time, decreased cost, and avoiding exposure to COVID. However, we need to ensure that we do not exacerbate existing health disparities for families that do not speak English and/or do not have the internet capabilities to support telemedicine technology.